Salivary cortisol and self-reported stress among persons with environmental annoyance - Carlsson, Frida; Persson, Roger; Karlson, Björn; Österberg, Kai; Hansen, Åse Marie; Garde, Anne Helene; Ørbæk, Palle (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'Increased vulnerability to stress has been suggested as a possible mechanism behind medically unexplained conditions such as sensitivity to electricity and common smells. This study examined whether subjective environmental annoyance among the general population is associated with increased physiological reactivity or subjective stress scores. ' ' METHODS ': 'Four groups were studied (N=141): an electrically annoyed (N=17), a smell-annoyed (N=29), and a generally annoyed group (N=39) and a reference group matched for age, gender, and socioeconomic status (N=56). Over 5 days, the participants collected saliva for cortisol determination at awakening, 30 minutes after awakening, 8 hours after awakening, and at 9 o’clock in the evening. On the evening preceding the fifth day, the participants ingested a 0.5-mg dexamethasone tablet so that possible differential suppression of the hypothalamic-pituitary-adrenal (HPA) axis could be assessed. Each day, the participants also rated their subjective stress and health complaints. ' ' RESULTS ': 'No significant differences were found between the groups regarding cortisol secretion over 5 days. The dexamethasone suppression test showed inhibited cortisol secretion in all four groups. No associations were found between the cortisol concentrations and the self-reported stress scores or subjective health complaints. ' ' CONCLUSIONS ': 'Although the environmentally annoyed groups showed no signs of increased HPA-axis activation, being annoyed by both electrical devices and smells seems to be related to increased psychological activation in terms of self-reported stress. Because the participants were otherwise healthy and recruited from the general population, the results imply that subtle psychological stress processes may be important in the early development of environmental annoyance.
Keywords: environmental annoyance; environmental illness; salivary cortisol; self-assessment; self-report; self-reported stress